2021
DOI: 10.1021/acssuschemeng.1c04706
|View full text |Cite
|
Sign up to set email alerts
|

Composition-Switchable Liquid Crystalline Nanostructures as Green Formulations of Curcumin and Fish Oil

Abstract: Green compositions and processes for fabrication of dual-and multi-loaded nanocarriers with antioxidant functionality and neuroprotective, cardioprotective, antiviral, and antiproliferative activities are of broad interest for innovations in pharmaceutics and nutraceutics. Co-encapsulation of curcumin (studied as a key multipurpose phytochemical antioxidant) with ω-3 polyunsaturated fatty acids (PUFAs) (studied as active ingredients of natural fish oil) may increase the oxidative stability of selfassembled for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 107 publications
(493 reference statements)
2
24
0
Order By: Relevance
“…The AFM images show that the sizes visualized are consistent with the sizes measured. Moreover, they suggest that SLN and NLC particles are spherically shaped which coincides with studies performed by Tetyczka et al ( Tetyczka et al, 2019 ) and Rakotoarisoa et al ( Rakotoarisoa et al, 2021 ) using cryo-transmission electron microscopy combined with synchrotron small-angle X-ray scattering. The shifts in the thermal profiles of the particles allowed identifying the type of lipid system present.…”
Section: Discussionsupporting
confidence: 88%
“…The AFM images show that the sizes visualized are consistent with the sizes measured. Moreover, they suggest that SLN and NLC particles are spherically shaped which coincides with studies performed by Tetyczka et al ( Tetyczka et al, 2019 ) and Rakotoarisoa et al ( Rakotoarisoa et al, 2021 ) using cryo-transmission electron microscopy combined with synchrotron small-angle X-ray scattering. The shifts in the thermal profiles of the particles allowed identifying the type of lipid system present.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, Rakotoarisoa et al. (2021) developed a cubic structure of liquid crystal nanoparticles for dual loading of fish oil and curcumin. The study found that as the moisture content increased, the structure of the liquid crystalline gradually transformed from cubes to a mixture of cubes and sponges.…”
Section: Different Types Of ω3 Pufas Encapsulation Systemmentioning
confidence: 99%
“…The addition of EPA caused the lipid membrane of monoolein to form sponges and nanosponges when the MO/EPA ratio was 3:7, and contained the EPA with the highest content at the same time. Recently,Rakotoarisoa et al (2021) developed a cubic structure of liquid crystal nanoparticles for dual loading of fish oil and curcumin. The study found that as the moisture content increased, the structure of the liquid crystalline gradually transformed from cubes to a mixture of cubes and sponges.…”
mentioning
confidence: 99%
“…Recent studies have used cryogenic transmission electron microscopy (cryo-TEM) coupled with small-angle X-ray scattering to characterize the morphology of nanostructures formed during structural transitions in amphiphilic mixtures. 12 14 The combination of these nanoscale characterization techniques was used to elegantly describe a transition from lipid vesicles to flattened sponge-like structures of bilayers containing pores. 12 Additionally, numerous studies have reported vesicle to micelle structural transitions in mixed amphiphilic systems.…”
Section: Introductionmentioning
confidence: 99%